Changes in dental fluorosis following the cessation of water fluoridation - Clark DC, Shulman JD, Maupome´ G, Levy SM. (Blackwell Synergy, 2006)
To determine changes in the prevalence of dental fluorosis, and in perceptions of aesthetic concerns due to dental fluorosis after water fluoridation ceased.